An Oil and Gas Model - Krichene, Noureddine (Washington, D.C. : International Monetary Fund, 2007)
This paper formulated a short-run model, with an explicit role for monetary policy, for analyzing world oil and gas markets. The model described carefully the parameters of these markets and their vulnerability to business cycles. Estimates showed that short-run demand for oil and gas was price- inelastic, relatively income-elastic, and was influenced by interest and exchange rates; short-run supply was price-inelastic. Short-run price inelasticity could be a source for high volatility in oil and gas prices, and could confer to producers a temporary market power. Being simultaneous and incorporating interest and exchange rates, the model could be useful in short-term forecasting of oil and gas outputs and prices under policy scenarios.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet